2005
DOI: 10.1089/vbz.2005.5.351
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tick-Borne Organisms in Mule Deer (Odocoileus hemionus) from the Western United States

Abstract: Free-ranging mule deer (MD; Odocoileus hemionus) from Arizona and California were tested for evidence of infection with several tick-borne pathogens, including species of Ehrlichia, Anaplasma, Babesia, and Borrelia. Of 125 mule deer tested from Arizona, 29 (23%) and 11 (9%) had antibodies reactive to E. chaffeensis and A. phagocytophilum by indirect immunofluorescent antibody testing, respectively; none of the six MD tested from California were seropositive. Using a commercial competitive ELISA kit, antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 50 publications
0
43
0
1
Order By: Relevance
“…Recent studies confirmed that free-ranging cervids and bovids are regular hosts of A. phagocytophilum strains in nature. Serological and/or molecular evidence of natural infection was reported in several cervid species in North America and Japan (Belongia et al, 1997;Little et al, 1998;Foley et al, 1998;Yabsley et al, 2005;Michalski et al, 2006;Kawahara et al, 2006). In Europe, infections in forest artiodactyls apparently occur throughout the continent.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed that free-ranging cervids and bovids are regular hosts of A. phagocytophilum strains in nature. Serological and/or molecular evidence of natural infection was reported in several cervid species in North America and Japan (Belongia et al, 1997;Little et al, 1998;Foley et al, 1998;Yabsley et al, 2005;Michalski et al, 2006;Kawahara et al, 2006). In Europe, infections in forest artiodactyls apparently occur throughout the continent.…”
Section: Discussionmentioning
confidence: 99%
“…are able to survive up to 35 days at 4°C in refrigerated blood and indefinitely under conditions of cryopreservation (163). Serologic studies of reservoir animals suggested seroprevalences of approximately 25% for B. microti in the white-footed mouse and approximately 35% in mule deer (98,164) and between 16 and 28% PCR positivity in peripheral blood of rabbits in areas of endemicity (110,153).…”
Section: Epidemiology and Transmission Dynamicsmentioning
confidence: 99%
“…Ehrlichia determinations for a subset of 24 test-positive and -negative samples were validated by comparison with the results of a PCR using a 16S nested primer set described by Yabsley et al (2005). The Ehrlichia/Anaplasma genera primary forward and reverse primers were 16S rRNA ECB 5 -CGTATTACCGCGG-CTGCTGGCA-3 and 16S rRNA ECC 5 -AGAACGAACGCTGGC-GGCAAGCC-3 , respectively (Dawson et al, 1994).…”
Section: Dna Extractionmentioning
confidence: 99%